STRATEGIC IMPACT OF EDWARD DEMING'S TQM PRINCIPLES ON A HEALTHY AND PRODUCTIVE ELEMENTARY SCHOOL ENVIRONMENT - Sari Febrianti; Alifa Syauqi Hatami; R Madhakomala (PIONIR: JURNAL PENDIDIKAN, 2025)
This study aims to analyze the strategic impact of Deming’s TQM principles on creating a healthy and productive elementary school environment, in SDN Pondok Pucung 3 Tangerang Selatan. This research employed a qualitative descriptive approach, with data collected through observation, in-depth interviews with the principal, teachers, and school committee members. The results reveal that the school has successfully implemented key TQM principles such as participatory leadership, the Plan-Do-Check-Act (PDCA) cycle, stakeholder involvement, and customer-oriented service. The commitment of the principal, together with the active participation of teachers, students, and the school committee, has significantly improved environmental cleanliness, reduced student absenteeism due to health issues, and fostered a culture of healthy and responsible behavior among the school community. The findings indicate that the application of Deming’s TQM principles not only enhances the efficiency of school management but also contributes to the creation of a healthy, safe, and productive learning environment. The strategic impact is continuous improvement, stakeholder collaboration, and process-focused leadership enhance student well-being and learning outcomes. Keywords: Deming’s TQM Principle, Elemetary School, Environment